Coverings for protection against fretting-corrosion - Ляшок, Светлана Викторовна (Eastern-European Journal of Enterprise Technologies, 2012)
Influence of multilayer vacuum-plasma coating (a-Ti+TiN)´5 and also coating from MoS2 on damage resistance of steel samples in conditions of fretting-corrosion has been investigated